Anesthetic management of off-pump simultaneous coronary artery bypass grafting and lobectomy: Case report and literature review. Issue 50 (December 2017) - Zhao, Xian; Li, Yuhong; Kong, Hai-Ying; Zhang, Lin; Wen, Xiao-Hong
Abstract: Rationale: Survey data show approximately 10% patients with lung cancer may present concomitant coronary heart disease. Simultaneous surgery is a challenge for anesthetist. We review our experience in the anesthesia with 5 patients who required simultaneous off-pump coronary artery bypass grafting (OPCABG) and pulmonary resection for lung cancer. Patient concerns: Between 2014 and 2016, 5 patients with ASA (American Society of Anesthesiologists) grade II or III, underwent combined OPCABG and lung resection in the first Affiliated Hospital, Zhejiang University School of Medicine. Diagnoses: All five patients were diagnosed with coronary heart disease and peripheral pulmonary carcinoma Interventions: Five patients received general anesthesia with double-lumen endobronchial tube for lung separation. The anesthetics were used, which caused slight hemodynamic fluctuations during induction of anesthesia; while during the maintenance of anesthesia, supplemented by Dexmedetomidine, the drug doses were titrated according to the depth of anesthesia. Guided by cardiac index (CI), stroke volume variation (SVV) and oxygen delivery (DO2 ), different strategies were taken at the different stage of surgery, during lung resection, SVV was kept about 13% to 15%, and less than 10% during OPCABG. Outcomes: Five patients were transferred to intensive care unit (ICU) with intubation after surgery, duration of ventilation was 10 to 18 hours, and length of ICU stay and hospital stay were 1.8 to 2.5 ds and 11 to 16 ds, respectively. All of patients were discharged with not any perioperative complication. Lessons: In summary, anesthetists should focus on the maintenance of the balance between oxygen supply and demanding, which was achieved by close monitoring, titration of anesthetics and goal-directed fluid therapy during surgical procedures.